(untitled) (Comprehensive Journal of Science, 2026)
This study aims to examine the role of human resource management in reducing work stress within banking institutions the study was conducted on a sample of commercial banks operating in wadi al shati (Bark al order branch) jumhouria bank (Barqan,qutha branch )the importance of this study arises from the challenges faced by the banking sector due to work stress experienced by employees which may negatively affect performance e levels and the quality of services provided despite the noticeable advancement in modern technologies the study also highlights the pivtal role of human resource management in utilizing human competencies and directing them in ways that improve the work environment and reduce occupational stress the study adopted the descriptive analytical approach and a questionnaire was used as the main tool for data collection it was distributed to a sample of 33 employees working in the banks under study the collected data were analyzed using SPSS the findings revealed a statistically significant relationship between human resource management practices and the reduction of work stress within banking institutions.